A TALE OF TWO VISIONS: Representing the Orientialized West, Representing the Orient. (2nd January 2018) - Cevik, Gulen
Abstract: Starting in the eighteenth century, the West's interest in the exotic was matched with a rival gaze from the East. The fluid seams where the so-called dualities met have generated powerful spaces of tension: Occident, Orient; master, colonized; and public, private. The elite Muslim Ottoman women's agency in dress via adoption of corsets, tight-fitting dresses and the adoption of overstuffed seating furniture modeled after the Turkish divan in the West resulted in an unprecedented conflict between furniture, the body and the dress. The inclusion of the body and its dress in the discourse helps to construct an interior design theory that deals with the immediate, experiential role of the body unlike the abstract body in space, which served architectural theory for centuries. Furthermore, the body fosters social manifestation of spaces. This is the fascinating story of a cultural exchange between women: an exchange of divans and corsets.